Adverse childhood experiences, re-trafficking vulnerability, and mental health outcomes among women survivors of human trafficking in Kampala, Uganda: A cross-sectional analysis - Violet Nkwanzi; Robert M. Bulamba; David Okech; Catherine Carlson; Emmanuel Kyasanku; Sylvia Namakula; Deneen Evans; Alex Daama; Stephen Mugamba; Dorah Akello; Emmanuel Menya; Jackline B. Nammanda; et al. (PLoS ONE, 2025)
Background Globally, human trafficking disproportionately affects women and girls, exposing them to severe exploitation and long-term psychological, social, and economic harm. While global efforts to prevent trafficking have intensified, the risk of re-trafficking remains a critical yet understudied issue in low-resource settings, particularly in Uganda. Uganda’s limited data on the effects of adverse childhood and re-trafficking vulnerabilities on the long-term mental health outcomes of survivors of trafficking limits the design of evidence-based interventions to improve survivors’ health. Our study examined the link between Adverse Childhood Experiences (ACE), re-trafficking vulnerability, and lasting mental health consequences among female survivors of human trafficking in Uganda Methods A cross-sectional study was conducted among 350 female survivors of human trafficking in Kampala, Central Uganda, in January 2025. Trained female research assistants conducted one-on-one interviews in English or Luganda, a local language. Data on participants’ socio-demographic characteristics, adverse childhood experiences (ACE-IQ), human trafficking vulnerability (AHTST), anxiety (GAD-7), depression (PHQ-9), and PTSD were collected. Bivariate and multivariable modified regression models with robust standard errors were performed using Stata version 17.0 for analysis Results Of the 350 female survivors of trafficking interviewed in Central Uganda, more than half (63.7%) reported experience of ACEs, 63.4% screened positive for human trafficking vulnerability, 57.1%, 56%, and 40.9% identified with anxiety, depression, and PTSD symptoms, respectively. Experience of ACEs strongly correlated with a 5%, 4%, and 6% increased risk of experiencing anxiety (aRR = 1.05, 95% CI: 1.02-1.08), depression (aRR = 1.04, 95% CI: 1.01-1.06), and PTSD (aRR =1.06, 95% CI: 1.03-1.09) symptoms, respectively. Additionally, age and education were strongly linked to a heightened risk of experiencing mental health (MH) symptoms among this population. Furthermore, trafficking vulnerabilities were paradoxically associated with lower symptom severity of all three MH conditions in this population Conclusion This study highlights the strong link between adverse childhood experiences (ACEs), re-trafficking vulnerability, and MH risks among trafficking survivors in Uganda. High ACE exposure significantly increases anxiety, depression, and PTSD risk. The results reveal the immediate need for trauma-informed interventions addressing ACEs and mental health to reduce re-trafficking risks and promote survivor resilience. Unexpectedly, greater trafficking vulnerability correlated with lower symptom severity, warranting further investigation.